Analisis pengaruh variable makroekonomi terhadap Foreign direct investment di indonesia - Azhar Najmuddin; Ratnawati Ratnawati; Octa Widya Pratiwi; Cep Jandi Anwar; Indra Suhendra (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine the effect of macroeconomic variables on Foreign Direct Investment in Indonesia. The independent variables used in this study are Gross Domestic Product, inflation, and exchange rates, while the dependent variable in this study is Foreign Direct Investment. The type of research used is explanatory research, with a quantitative approach. The types and sources of data used are secondary data in the form of time series accessed on the official website of Bank Indonesia in the1period 2010 to 2022 which are processed into quarterly1data with a sample of 52 samples. The data analysis technique in this study uses multiple linear regression analysis. The results of this study indicate that GDP and inflation partially have a positive effect on FDI. While the exchange rate partially has no significant effect on FDI. Simultaneously, the independent variable has no significant effect on the dependent variable.